EFFECTS OF MATCH FORMS AND OUTCOMES ON THE PHASE-BASED ELITE MALE TABLE TENNIS MATCH PERFORMANCE (Kinesiology, 2022)
The aim of the study was to explore the service round technical-tactical performance indicators of three phases discriminating the match result and the two match forms. The statistics of 72 professional men’s singles matches of the 2018 international competitions were collected. A chi-square test was used to assess the relationship between match form, match outcome and service round result. Afterwards, a two-way ANOVA was performed to evaluate the effect of match form (SHM: match between players of the same handedness and OHM: match between players of the opposite handedness) and match result on three evaluation indices of thirteen technical-tactical indicators. The results displayed that: (1) there was a weak relationship between the service round outcome and match form for both the winning and losing players (p